2009
DOI: 10.1007/s12033-009-9147-y
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Vibrio anguillarum Ghost by Coexpression of PhiX 174 Lysis E gene and Staphylococcal Nuclease A Gene

Abstract: Vibrio anguillarum ghosts (VAG) were generated, for the first time, using a conjugation vector containing a ghost bacteria inducing cassette, pRK-lambdaP(R)-cI-Elysis, in which the expression of PhiX174 lysis gene E was controlled by the P ( R )/cI regulatory system of lambda phage. By scanning electron microscopy, holes ranging 80-200 nm in diameter were observed in the VAG. To avoid the presence of bacterial genomic DNA and an antibiotic resistance gene in the final VAG product, we constructed a new dual vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Plasmid pRKkPR-cI-E-SNA bearing the bacteriophage PhiX174 lysis E gene was introduced into normal E. coli S17-1 cells to produce E. coli ghosts (42). Although these E. coli cells are preyed upon by B. bacteriovorus 109J, their ghosts were not recognized as prey when added to a fresh culture of AP B. bacteriovorus 109J.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmid pRKkPR-cI-E-SNA bearing the bacteriophage PhiX174 lysis E gene was introduced into normal E. coli S17-1 cells to produce E. coli ghosts (42). Although these E. coli cells are preyed upon by B. bacteriovorus 109J, their ghosts were not recognized as prey when added to a fresh culture of AP B. bacteriovorus 109J.…”
Section: Resultsmentioning
confidence: 99%
“…More than 80 serotypes of V. parahaemolyticus have been described worldwide, based on the O and K antigenic properties [22]. To date, some BGs have been produced from other Vibrio species ( V. cholera , V. anguillarum , V. vulnificus ) by using the lysis E -gene system [4,5,23,24], but no BGs have been reported from V. parahaemolyticus . In the present study, we determined the MIC of various chemicals (six acids and one alkali) on V. parahaemolyticus cells and characterized their efficiencies to produce V. parahaemolyticus ghosts (VPGs).…”
Section: Introductionmentioning
confidence: 99%
“…Even highly sensitive and fragile structures such as pili can be well protected by this technology (Eko et al, 2000). The potential usefulness of bacterial ghosts as vaccine candidates against a wide variety of pathogenic Gram-negative bacteria (Ra et al, 2009), such as EHEC O157 Cai et al, 2010), EPEC E2348/69 (Liu et al, 2012), Vibrio anguillarum (Kwon et al, 2009), Aeromonas hydrophila and Edwardsiella tarda (Lee et al, 2008;Wang and Lu, 2009), has recently been widely reported. However, production and characterization of bacterial ghosts for a vaccine candidate against an intracellular bacterial pathogen, such as Brucella, have not been reported.…”
Section: Introductionmentioning
confidence: 99%